Impact of Change in Body Mass Index on Outcomes After Left Ventricular Assist Device Implantation in Obese Patients. Issue 7 (September 2019) - Mano, Akiko; Kilic, Ahmet; Lampert, Brent C.; Smith, Sakima A.; Whitson, Bryan; Hasan, Ayesha K.
Abstract : Obesity could be a risk factor portending a poor prognosis after left ventricular assist device (LVAD) implantation. We sought to determine the impact of change in body mass index (BMI) on outcomes in obese patients supported by LVAD. Fifty-nine patients, who received LVAD between January 2010 and June 2015, with BMI ≥30 kg/m 2 at the time of LVAD implantation, were retrospectively analyzed. Patients were divided into two groups based upon whether BMI after 6 months of device support decreased when compared with before. Thirty-eight patients who experienced decrease in BMI (group D) were compared with 21 patients whose BMI increased (group I). Baseline characteristics were similar between the groups except for body weight and BMI, which were significantly higher in group D (BMI: 35.9 ± 4.0 kg/m 2 vs. 33.4 ± 3.5 kg/m 2 ; p = 0.018). During mean follow-up of 560 ± 178 days, group I had significantly higher incidence of infection [events per patient-years (eppy): nondevice related: 0.18 vs. 0.35, p = 0.01; device related: 0.1 vs. 0.32, p < 0.01; sepsis: 0.1 vs. 0.32, p < 0.01], heart failure (eppy: 0.1 vs. 0.25, p < 0.01), and renal failure (eppy: 0.03 vs. 0.14, p < 0.01). Survival at 2 years was significantly lower in group I (84.8% vs. 57.1%, p = 0.025). Increase in BMI in obese patients on LVAD is associated with worse survival with a higher incidence of infection, heart failure, and renal failure. Weight control may be a modifiable factor to improve prognosis.